Dechema chemistry data series : vapor liquid equilibrium data collection ketones (supplement 1) - Gmehling, J.; Onken, U.; Rarey, J. R. (Frankfurt Dechema, 1993)
part 3b
Keywords: Vapor-Liquid equilibrium; Binary mixtures -- Data tables and diagrams; Ketones